2015
DOI: 10.1039/c5cp04360c
|View full text |Cite
|
Sign up to set email alerts
|

Trap-limited charge recombination in intrinsic perovskite film and meso-superstructured perovskite solar cells and the passivation effect of the hole-transport material on trap states

Abstract: Charge recombination dynamics in intrinsic perovskite film and in meso-superstructured perovskite solar cells have been systematically studied, which are found to be mediated by the energetic distribution of intra-gap trap states as described by the trap-limited recombination theory. Besides, the passivation effect of the hole-transport material on trap states is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In most common lead halide perovskites, the A position represents an organic or metal cation, e.g., methylammonium (MA + ), formamidinium (FA + ), and Cs + , which should be large enough to meet the tolerance factor t due to the large radius of Pb 2+ in the B position, while the C positions are halogen anions or their mixtures, which forms the 3D perovskite structure . The crystal structure provides the fantastic properties of perovskite materials, such as long carrier recombination lifetime, wide absorption of light, long exciton diffusion length, high charge mobility, which has led perovskites to be popular in photovoltaic applications …”
Section: Introductionmentioning
confidence: 99%
“…In most common lead halide perovskites, the A position represents an organic or metal cation, e.g., methylammonium (MA + ), formamidinium (FA + ), and Cs + , which should be large enough to meet the tolerance factor t due to the large radius of Pb 2+ in the B position, while the C positions are halogen anions or their mixtures, which forms the 3D perovskite structure . The crystal structure provides the fantastic properties of perovskite materials, such as long carrier recombination lifetime, wide absorption of light, long exciton diffusion length, high charge mobility, which has led perovskites to be popular in photovoltaic applications …”
Section: Introductionmentioning
confidence: 99%
“…There are many works aiminga telucidating the charge-carrier recombination mechanism in intrinsic perovskite films using av ariety of techniques, such as photo-induced terahertz absorptions pectroscopy, [8] time-resolved photoluminescence decay, [9,10] and transient absorption spectroscopy. [11] The monomolecular (trap-assisted), bimolecular( band-to-band), and Auger recombination processes were observed and analyzed by varying the excitation intensity with different perovskites and structures. Accordingly,h igh excitation intensity tends to trigger high-order dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] In recent years, we have reported that time-resolved charge extraction (TRCE) could act as another effective candidate to study quantitatively the DOS distribution in dye-sensitized solar cells, quantum-dot-sensitized solar cells, and perovskite solar cells. [56][57][58][59][60] However,asignificant limitation of these methods is that the tested system should be connected to as hort or open circuit,s ot hey are unable to investigate the trap states in intrinsic perovskite films without selected electrodes. In contrast, transient infrareda bsorption spectroscopy can be used to measure the DOS distribution of thin films, but it is not easy to identify the characteristic optical signals and the requirement of instrumentsa nd technology is relatively high.…”
Section: Introductionmentioning
confidence: 99%